Indirect Spectrophotometric Determination of Tolterodine Tartrate in Pure and Pharmaceutical Preparations - M. Fraihat, Safwan; S. Khatib, Hatem (Asian Journal of Chemistry, 2012)
Two simple, accurate, sensitive and economical procedures for the estimation of tolterodine tartrate (TOL) both in pure and in pharmaceutical formulations have been developed. The first method (A) was based on the oxidation of the studied drug by a known excess of cerium(IV) as an oxidizing agent and subsequent determination of unreacted oxidant by reacting it with (methylene blue) dye, while the second method (B) involved N-bromosuccinimide (NBS) as an oxidant and (indigo) dye. The absorbance values were determined at 660 and 610 nm, respectively. The reacted oxidant corresponds to the drug content. Regression analysis of Beer-Lambert plots showed good correlations in the concentration ranges 5-18 and 38-80 μg/mL for methods A and B, respectively. The molar absorptivity, Sandell sensitivity, detection and quantification limits were calculated. The optimum reaction conditions and other analytical parameters were evaluated. The proposed methods were applied to the determination of tolterodine tartrate in pharmaceutical formulations. The results have demonstrated that the methods are equally accurate and reproducible as the official methods.